Pre- and post-hatching factors affecting juvenile growth rates inthe yellow-spotted river turtle (Podocnemis unifilis). (2004)
ABSTRACT: Podocnemis unifilis eggs obtained from the Cahuinarí National Park, Colombia were incubated artificially under constant temperatures during two nesting seasons. A sample of the hatchlings produced were sexed to document the pivotal temperature for this population (32 °C). It appears that during both nesting seasons, most nests on the study beach produced individuals of each sex. The remaining turtles obtained in the laboratory were reared for one year in order to study the effects of pre- and post-hatching factors on their growth rates. We documented maternal effects on egg sizes and initial hatchling sizes each year, but not on subsequent juvenile growth rates. Incubation condition influenced both initial hatchling sizes and growth rates, with turtles from the high temperature condition emerging at smaller initial sizes and then demonstrating higher growth rates. By the end of the first year, these individuals were significantly larger than their siblings that had experienced cooler incubation temperatures, which is consistent with predictions of the Charnov and Bull hypothesis concerning the adaptive value of temperature-dependent sex determination. We also examined the effects of diet, density, and basking opportunities on growth rates, and found that turtles that received meat in their diets grew faster than those feed only vegetable matter. Turtles in the low density condition attained larger sizes in one of the two years of the study, while access to direct sunlight for basking did not significantly alter growth rates.